Ageing population and health care expenditure: Evidence using time series analysis - Roziana Baharin,; Suhaila Saad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study is conducted to examine the relationship between population agieng and its effects on total health expenditure since there has been less attention given in analysing this issue particularly in developing countries. Thus, the study covers a period from 1995 to 2014 and was analysed in 3 countries in Southeast Asia; Malaysia, Indonesia, and Thailand. This study applies Autoregressive Distributed Lag (ARDL) method with Bound test approach to examine the existance of cointegration in the model. Apart from that Vector Error Correction Model (VECM) was also estimated to investigate the short run nexus. For validation and appropriate model specification purpose, different econometric diagnostic tests were applied. The motivation of this study is to shed some light on the growing concern of raising ageing population across the world and the burden carried with it, namely health expenditure. The result of this study supports previous studies where increasing numbers of ageing population has significantly affect health expenditure in Malaysia and Indonesia while in the case of Thailand its remains insignificant. The ageing does not affect health expenditure in Thailand probably due the fact that major healthcare provider in Thailand is private sector which implies that health expenditure are mostly determined by the affordability of population to pay for health services. Thus, in order to ensure that raising of ageing population would not increase the burden via health expenditure, the government should embark on the education campaign to encourage a healthy life style among adulthood since they were young.